Immune cells participate in the oncosuppressive activity of parvovirus H-1PV and are activated as a result of their abortive infection with this agent - Grekova, Svitlana; Aprahamian, Marc; Giese, Nathalia; Schmitt, Steffen; Giese, Thomas; Falk, Christine Susanne; Daeffler, Laurent; Cziepluch, Celina; Rommelaere, Jean; Raykov, Zahari Zahariev (Cancer biology & therapy, 2010)
Treatment of cancers by means of viruses, that specifically replicate in (oncotropism) and kill (oncolysis) neoplastic cells, is increasingly gaining acceptance in the clinic. Among these agents, parvoviruses have been shown to possess not only direct oncolytic but also immunomodulating properties, serving as an adjuvant to prime the immune system to react against infected tumors. Here, we aimed to establish whether immunomodulating mechanisms participate in the recently reported therapeutic potential of parvoviruses against pancreatic carcinoma. Using adoptive transfer experiments we discovered that the transfer of splenocytes of donor rats harboring H-1PV-treated orthotopic PDAC tumors could significantly prolong the survival of naïve tumor-bearing recipients, compared to those receiving cells from mock-treated donors. Closer investigation of immunological parameters in infected donor rats revealed that virus-induced interferon gamma production and cellular immune response played an important role in this effect. These data have also preclinical relevance since abortive H-1PV infection of human peripheral blood mononuclear cells or cocultivation of these cells with H-1PV-preinfected pancreatic cancer cells, resulted in enhancement of innate and adaptive immune reactivity. Taken together our data reveal that oncolytic H-1PV modulates the immune system into an anticancer state, and further support the concept of using parvoviruses in the fight against pancreatic cancer.